2003
DOI: 10.1074/jbc.m210318200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Raf-1 by p21-activated Kinase 1 and Src Regulates Raf-1 Autoinhibition

Abstract: Exposure of cells to mitogens or growth factors stimulates Raf-1 activity through a complex mechanism that involves binding to active Ras, phosphorylation on multiple residues, and protein-protein interactions. Recently it was shown that the amino terminus of Raf-1 contains an autoregulatory domain that can inhibit its activity in Xenopus oocytes. In the present work we show that expression of the Raf-1 autoinhibitory domain blocks extracellular signal-regulated kinase 2 activation by the Raf-1 catalytic domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 33 publications
5
94
0
Order By: Relevance
“…Our finding that the S365A mutation increases not only the biological activity of B-Raf wt but also rescues that of B-Raf with a neutralized N-region (Figure 3b and c) strongly supports a model in which a major function of the N-region is to oppose the transition into an inactive conformation stabilized by binding of a 14-3-3 dimer to S365 and S729. Our model (Figure 9a), similar to that suggested by Mercer and Pritchard (2003), is consistent with recent studies showing that the negatively charged N-region of Raf-1 relieves autoinhibition by the N-terminal moiety owing to its reduced affinity towards a CR3 with a charged N-region (Cutler et al, 1998;Tran and Frost, 2003). However, we accept that similar experiments led to the alternative conclusion that the charged N-region induces a conformational change that does not affect the interaction between N-and C-terminal moiety but renders the CR3 resistant to the autoinhibition imposed by the N-terminal moiety (Chong and Guan, 2003).…”
Section: Regulation Of B-raf Signallingsupporting
confidence: 92%
“…Our finding that the S365A mutation increases not only the biological activity of B-Raf wt but also rescues that of B-Raf with a neutralized N-region (Figure 3b and c) strongly supports a model in which a major function of the N-region is to oppose the transition into an inactive conformation stabilized by binding of a 14-3-3 dimer to S365 and S729. Our model (Figure 9a), similar to that suggested by Mercer and Pritchard (2003), is consistent with recent studies showing that the negatively charged N-region of Raf-1 relieves autoinhibition by the N-terminal moiety owing to its reduced affinity towards a CR3 with a charged N-region (Cutler et al, 1998;Tran and Frost, 2003). However, we accept that similar experiments led to the alternative conclusion that the charged N-region induces a conformational change that does not affect the interaction between N-and C-terminal moiety but renders the CR3 resistant to the autoinhibition imposed by the N-terminal moiety (Chong and Guan, 2003).…”
Section: Regulation Of B-raf Signallingsupporting
confidence: 92%
“…interaction of Raf-1 with MEK (32,33). We found that RKTG overexpression inhibited Raf-1 Ser-338 phosphorylation in response to EGF (Fig.…”
Section: Rktg Changes the Subcellular Localization Of Raf-1 To The Golgimentioning
confidence: 71%
“…338 , and substitution of this site with alanine precludes Raf-1 activation by physiologic stimuli (34 -39). Phosphorylation of this site contributes to Raf-1 activation by blocking the ability of the Nterminal autoinhibitory domain to negatively regulate Raf-1 catalytic activity (28,29). Because this residue is conserved among Raf family members (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, the activation requirements of B-Raf are similar to those of Raf-1 because Raf-1 must also bind to Ras and requires phosphorylation of sites within the activation loop of its catalytic domain (Thr 491 and Ser 494 ) (27). However, full activation of Raf-1 also requires phosphorylation of Ser 338 and Tyr 341 , which lie outside the catalytic domain and contribute to the Raf-1 activation mechanism by blocking the actions of the autoinhibitory do-main (28,29). Interestingly, the residues in B-Raf corresponding to Tyr 340 and Tyr 341 in Raf-1 are substituted with aspartic acids, and Ser 445 , which corresponds to Ser 338 in Raf-1, appears to be constitutively phosphorylated in COS and PC12 cells (30).…”
mentioning
confidence: 99%